Pengujian Black Box pada Aplikasi Website Accurio Pro Print Manager Konica Minolta Menggunakan Teknik Equivalence Partition - Usep Irvan Nugraha; Mochamad Ihwan Ridwan Faturrohman; Awaludien Saputra; Rio Anggara; Aries Saifudin; Sri Mulyati (Jurnal Informatika Universitas Pamulang, 2021)
To find out that the Accurio Print Manager website application does not have an error / dysfunction, a test is carried out to minimize losses. Tests are carried out using the Black box method to find out wh ether from a functional point of view there are errors. The Equivalence Partition technique is carried out as a test so that when input is carried out it will produce the same output. Test cases are carried out to see whether an input will be responded to as expected or even vice versa.